Mengingat Dia yang Dikorbankan : Tafsir Feminis terhadap Hakim-hakim 11:1-40 - Firman Panjaitan; Dwi Ratna Kusumaningdyah (Studia Philosophica et Theologica, 2020)
Injustice, including gender issues, grows out of the abuse of power possessed by the authorities, which in turn results in victims, who are usually groups without power, both socially and theologically. The study in this article will discuss the Book of Judges 11: 1-40 which illustrates the dynamics in the life of Jephthah, who was a victim of society at first but due to the services he provided to Israel, he turned into a leader. But the story also illustrates that at the beginning of his power as a leader, Jephthah became the leader who sacrificed his own daughter; and the most interesting thing here is that all events occur by 'involving' the Spirit of the LORD. Thus the victim cycle produces victims into a clear picture in the judgment of Judges 11: 1-40.